Assessing the potential for synergies in the implementation of payments for environmental services programmes: An empirical analysis of Costa Rica - Zhang, Wei; Pagiola, Stefano (Cambridge University Press, 2011)
Payments for environmental services (PES) have been recognized as a promising mechanism for conservation, with the potential to contribute to social objectives such as poverty reduction. This paper outlines a simple framework for assessing the potential for synergies in the implementation of PES programmes, used to analyse the new watershed conservation funding (WCF) channelled through Costa Rica's national PES programme, Pago por Servicios Ambientales (PSA). The WCF financing can only be used in a limited number of watersheds. Given this constraint, the paper examines the mechanisms by which the WCF may potentially contribute to biodiversity conservation and to reducing social development gaps. Although there is significant spatial correlation among the priority areas targeted for the objectives of watershed conservation, biodiversity conservation and social development, the availability of the WCF per unit of land in most watersheds is limited compared to the PSA programme's prevailing payment rate of US$ 64 ha−1, potentially hindering the impact of the WCF on conservation and social development. The analysis helps guide the allocation of the PSA budget in a way that complements the WCF and improves the cost-effectiveness of the PSA budget.